2018
DOI: 10.3390/ijerph15010072
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Potential New Tobacco Control Regulations among U.S. Adults

Abstract: Favorable attitudes towards tobacco control policies can facilitate their implementation and success. We examined attitudes toward four potential U.S. Federal tobacco regulations (banning menthol from cigarettes, reducing nicotine levels in cigarettes, banning candy and fruit flavored electronic cigarettes, and banning candy and fruit flavored little cigars and cigarillos) and associations with individual and state variables. A nationally representative phone survey of 4337 adults assessed attitudes toward pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…Positions that would be popular among people indulging in one or more of the unhealthy behaviors would either be that (a) if controls are needed, the weakest ones would be the most acceptable, or (b) if strong regulation is needed, then sanctions for violations should not be too severe [18]. This position would be close to the "free-trade libertarian" view suggested by Goode [32].…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Positions that would be popular among people indulging in one or more of the unhealthy behaviors would either be that (a) if controls are needed, the weakest ones would be the most acceptable, or (b) if strong regulation is needed, then sanctions for violations should not be too severe [18]. This position would be close to the "free-trade libertarian" view suggested by Goode [32].…”
Section: The Present Studymentioning
confidence: 99%
“…As for tobacco control policies, it has been found that non-smokers, ex-smokers, women, older participants, and participants with non-conservative political views were more supportive of them than smokers, men, younger participants, and participants with conservative views [15][16][17][18]. The impact of educational and socio-economic level on support has, however, been more difficult to assess [19].…”
mentioning
confidence: 99%
“…Ainsi, un appui impor tant de la population a contribué au suc cès de plusieurs projets législatifs de lutte contre le tabagisme 9,10 , alors que, comme l'ont souligné Chen et ses collaborateurs 11 , un moindre appui du grand public a rendu les décideurs plus sensibles aux intérêts de l'industrie du tabac 12 . À l'échelle inter nationale, des équipes de recherche ont récemment examiné le soutien de la population envers certains types particuli ers d'interventions de lutte antitabac (campagnes médiatiques contre le taba gisme 13 et mises en garde illustrées sur les paquets de cigarettes 14 aux ÉtatsUnis), ainsi que l'appui envers les politiques antitabac au sein de certains groupes de population (fumeurs au Canada 15 , adoles cents à Hong Kong 11 et adultes aux États Unis 16 , en Finlande 17 et en Malaisie 18 ).…”
Section: Introductionunclassified
“…antismoking media campaigns 13 and pictorial warnings on cigarette packs 14 in the United States of America); and support for tobacco control policies among specific population groups (i.e. smokers in Canada, 15 adolescents in Hong Kong 11 and adults in the USA, 16 Finland 17 and Malaysia 18 ).…”
mentioning
confidence: 99%